Epidermodysplasia verruciformis associated with neurological and skeletal defects. - Agarwal, S.; Chander, R.; Sharma, S. (European Journal of Pediatric Dermatology, 2017)
Epidermodysplasia verruciformis (EV) is a rare genetic disorder characterized by immune dysregulation resulting in disseminated infection by human papillomavirus (HPV) and cutaneous malignancies. Associated mental retardation has been reported in a few patients. We report a unique case of a 10-year old boy with pityriasis versicolor-like and plane wart-like lesions. The skin lesions were associated with mental retardation, sixth cranial nerve palsy, pes planus, and spina bifida. The case is reported to highlight a possible predisposition of patients with EV to certain neurological and skeletal defects.